Biogas, agricultural biogas and biogas plants in Poland - selected statistical and legal aspects - Rosicki, Remigiusz; Rosicki, Grzegorz (Fundacja na rzecz Czystej Energii (FNCE), 2014)
Poland’s situation in the years 2012/2013 was far from stable and predictable in terms of legal regulations regarding the energy sector. Negative assessment of the works on necessary changes to the energy law does not refer to the scope of the subject. The scope of the subject of such works was forced by the need to adjust the requirements of the European Union in regards to the functioning of RES market. The prolongation of the works on regulations regarding the energy industry was also due to measures taken by various interest groups who, using this opportunity, attempted to guarantee their privileged "legal position” (RES sector, various types of RES, conventional energy sector). All these elements contributed to lack of the sense of legal stability. The object of analysis in the text is one of the RES sectors, namely the sector of biogas and agricultural biogas. Biogas, agricultural biogas and energy and/or heat obtained from them are not a significant element in the aspect of volume (power installed within RES is 136.3 MW, which constitutes 2.9%). However, attention must be drawn to major development potential of e.g. installations related to agricultural biogas production. The text presents the analysis of: (1) biogas potential in Poland, (2)definition of biogas and agricultural biogas, (3) development opportunities for biogas and agricultural biogas, (4) selected legal problems. The last case focuses on de lege ferenda regulations in the aspect of: (1) business activities involving generation of “energy” and agricultural biogas, (2) connection of RES/biogas installation to the transmission infrastructure. Due to specific dynamics of changes to the works on draft statutes, this part of the text focuses exclusively on signaling the selected legal institutions.
Biogaz, Biogaz rolniczy i biogazownie w Polsce – wybrane aspekty statystyczne i prawne
Keywords: biogaz; biogas; biogaz rolniczy; agricultural biogas; biogazowie; biogas plants; polityka energetyczna; energy policy; prawo energetyczne; energy law; bezpieczeństwo energetyczne; energy security